Sacred and Funeral Terracotta Figurines in Africa Proconsularis, Numidia and Mauretania Caesariensis between the First and Third Centuries CE - (:unkn) unknown (My University, 2019)
About 850 terracotta figurines have been found in Roman Africa since the late nineteenth century, in various contexts. Based on this large quantitative database, similarities and differences between figurines found in sacred and funeral contexts will be analyzed. Likewise, we will see how the figurines’ spatial analysis at different scales (provinces, necropolis, graves), the anthropological studies, the meticulous observations of the ritual gestures on the objects (breaking and reversal) and the figurines’ association into a tomb contribute to the interpretation of their function and allow to move past the initial image conveyed by these figurative materials.
Keywords: African Research